Is the bone tissue of the femoral neck demineralisedin patients with hip fracture? - Cano-Porras, Juan Ramón; Crespo, PV; Cruz, Encarnación; Rivas-Ruiz, Francisco; Sanchez Quevedo, MC; Guerado-Parra, Enrique; Campos, A (Elsevier, 2020)
The aim of this study is to establish the falsifiability of the "osteoporotic hypothesis" for hip fracture, according to which the bone density and mineral composition of bone tissue in patients with hip fracture is poorer than when no such fracture is present, and that this circumstance is relevant to the occurrence of a fracture. The study population consisted of forty patients treated with arthroplasty. Twenty patients with femoral neck fracture and another twenty with hip osteoarthritis received the same diagnostic protocol and the same antibiotic, anaesthetic, surgical and antithrombotic prophylaxis. Levels of calcium (Ca), phosphorus (P) and vitamin D in blood, amongst other values, were determined, and five samples of bone tissue from the proximal femoral metaphysis were obtained and characterised by optical microscopy and microanalytical analysis. No statistically significant differences were observed between the two groups with respect to the trabecular number, area or thickness, or inter-trabecular distance. However, there were differences in the length of the trabeculae, which was greater in the patients with hip osteoarthritis (p = 0.002), but not when the groups were compared by gender. When compared by age, a greater inter-trabecular distance was observed in the patients aged over 75 years (p = 0.036) but there were no differences in the remaining parameters. Serum levels of Ca (p = 0.03), P (p < 0.01) and vitamin D (p < 0.01) were lower in the fracture group. In the quantitative microanalytical analysis, no significant differences were observed in bone levels of Ca or P or in the Ca/P index, nor was there any correlation between serum and levels of bone Ca or P (Ca-0.197:p = 0.314;P-0.274:p = 0.158).Multiple linear regression revealed no correlation between the diagnoses, vitamin D and bone levels of Ca or P.
Keywords: Cadera - Cirugía; Bone metabolism; Hip fracture; Hip osteoarthritis; Microstructural trabecular bone; Mineralisation; Osteoporosis; Surgical treatment